Regulatory T Cells in Autoimmune Vasculitis - Jin, Ke; Parreau, Simon; Warrington, Kenneth J.; Koster, Matthew J.; Berry, Gerald J.; Goronzy, Jörg J.; Weyand, Cornelia M. (Frontiers in Immunology, 2022)
Abstract Blood vessels are indispensable for host survival and are protected from inappropriate inflammation by immune privilege. This protection is lost in patients with autoimmune vasculitides, a heterogeneous group of diseases causing damage to arteries, arterioles, and capillaries. Vasculitis leads to vascular wall destruction and/or luminal occlusion, resulting in hemorrhage and tissue ischemia. Failure in the quantity and quality of immunosuppressive regulatory T cells (Treg) has been implicated in the breakdown of the vascular immune privilege. Emerging data suggest that Treg deficiencies are disease-specific, affecting distinct pathways in distinct vasculitides. Mechanistic studies have identified faulty CD8+ Tregs in Giant Cell Arteritis (GCA), a vasculitis of the aorta and the large aortic branch vessels. Specifically, aberrant signaling through the NOTCH4 receptor expressed on CD8+ Treg cells leads to rerouting of intracellular vesicle trafficking and failure in the release of immunosuppressive exosomes, ultimately boosting inflammatory attack to medium and large arteries. In Kawasaki’s disease, a medium vessel vasculitis targeting the coronary arteries, aberrant expression of miR-155 and dysregulated STAT5 signaling have been implicated in undermining CD4+ Treg function. Explorations of mechanisms leading to insufficient immunosuppression and uncontrolled vascular inflammation hold the promise to discover novel therapeutic interventions that could potentially restore the immune privilege of blood vessels and pave the way for urgently needed innovations in vasculitis management.